Influence of Religiosity on HIV Risk Behaviors among College Students - Rezki Perdani Sawai; Dini Farhana Baharudin; Muhammad Khairi Mahyuddin (2024)
Emerging new research show that spirituality and religion can act as important preventive and therapeutic resources for a wide number of diseases. There is also proof that there is a positive relationship between religiosity and the practice of protective health behaviors in previous literatures. This study aims to examine how religiosity influences AIDS prevention by testing whether participants’ religiosity scores explain their risky decisions associated with drug use, sex and condom use among a sample of college students in Kuala Lumpur, Malaysia. Using the Muslim Religiosity and Personality Assessment Inventory, it is hypothesized that participants with higher religiosity scores were more likely to abstain from HIV risk behaviors. Implication of the findings has significance in directing HIV/AIDS prevention policy.